One Country, Two Systems : Evidence on Retirement Patterns in China - Giles, John T.; Lei, Xiaoyan; Wang, Gewei; Wang, Yafeng; Zhao, Yaohui (World Bank, Washington, DC, 2021)
This paper documents the patterns and correlates of retirement in China using a nationally representative survey, the China Health and Retirement Longitudinal Study. After documenting stark differences in retirement ages between urban and rural residents, the paper shows that China's urban residents retire earlier than workers in many Organisation for Economic Co-operation and Development countries and that rural residents continue to work until advanced ages. Differences in access to generous pensions and economic resources explain much of the urban-rural difference in retirement rates. Fending off the fiscal pressures resulting from rapid population aging will require encouraging longer working lives among more highly educated and skilled workers living in China's urban areas. The paper suggests that reducing disincentives created by China's employee pension system, improving health status, providing childcare, and elder care support may all facilitate longer working lives. Given spouse preferences for joint retirement, creating incentives for women to retire later may facilitate longer working lives for men and women.